Clinical trials for cellular therapy products: conclusions reached by foreign regulatory bodies - E. V. Melnikova; O. V. Merkulova; V. A. Merkulov (Вестник трансплантологии и искусственных органов, 2020)
Currently, the problem of adopting viable human cell-based drugs – biomedical cell products (BCPs) – in medical practice in the Russian Federation includes, among others, lack of experience in clinical trials for such drugs and insufficient expert assessment under the national state registration procedure. In global practice, by the beginning of 2020, there were over 30 cellular therapy products (human cellular- and tissue-based products) known to have undergone clinical trials for sales licenses from regulatory bodies in the United States, European Union, Japan, and South Korea. Most cellular therapy products are intended for treatment of severe orphan diseases and lifethreatening conditions that currently cannot be treated by traditional drugs or methods. The aim of this study is to analyze the global experience in clinical trials for cellular therapy products and also to examine conclusions reached by regulatory authorities with regards to issuance of sales licenses for the products. Particular attention was paid to clinical trials that subsequently led to granting of sales license (state registration). In reviewing such trials, we also focused on the types and number of clinical trials, the number of patients involved in the clinical trials, conclusions made by expert regulatory agencies on the efficacy, safety and risk/benefit ratio. Most of the products were approved for use based on uncontrolled phase II clinical trials. In the clinical trial, apart from the historical group and the placebo-controlled group, there was also a control group that received nothing. The number of patients in most clinical trials was limited, especially for drugs intended for treatment of rare genetic diseases, as well as drugs approved for use in Japan.